Monkey Dance Transformation And Displacement: From Traditional Performance To Urban Everydayness - Anton Sutandio (Bina Nusantara University, 2012)
This research attempts to investigate how the monkey dance, a traditional mobile performance from village to village, transforms and displaces itself into a semi-permanent urban street performance as the effect of modernization and globalization. The research is closely relevant to the theme of the everyday life on the relation between art and the social. Doger monyet (monkey dance) performance has always been regarded as the marginal art/culture. Its place has always been among the mid-lower class of society, thus when it changes its mode and place of performance, questions and curiosity arises. This phenomenon requires a re-examination of the cultural transformation effect to everyday life. This research attempts to answer several issues regarding the phenomena: how the performance negotiates its way to the urban everyday life and its everydayness; how it manages to place itself within the urban space; how it deals with the authority and the urban dwellers, and what its future is going to be like in the new space.